2020
DOI: 10.3390/min11010022
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, Mineralogy and Microbiology of Cobalt in Mining-Affected Environments

Abstract: Cobalt is recognised by the European Commission as a “Critical Raw Material” due to its irreplaceable functionality in many types of modern technology, combined with its current high-risk status associated with its supply. Despite such importance, there remain major knowledge gaps with regard to the geochemistry, mineralogy, and microbiology of cobalt-bearing environments, particularly those associated with ore deposits and subsequent mining operations. In such environments, high concentrations of Co (up to 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 120 publications
0
12
0
3
Order By: Relevance
“…Ziwa et al. (2021) concluded that Co mobility in mine wastes is typically controlled by precipitation and co‐precipitation as hydroxides and sulfates. These processes may contribute to Co mobility in Faro waste‐rock pile; however, the secondary mineralogical control on Co mobility is the subject of an ongoing assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziwa et al. (2021) concluded that Co mobility in mine wastes is typically controlled by precipitation and co‐precipitation as hydroxides and sulfates. These processes may contribute to Co mobility in Faro waste‐rock pile; however, the secondary mineralogical control on Co mobility is the subject of an ongoing assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Bao et al (2021) found that Pb mobility is largely retained due to formation of Pb-bearing carbonates (i.e., cerussite, and shannonite) in the waste-rock pile. Ziwa et al (2021) concluded that Co mobility in mine wastes is typically controlled by precipitation and co-precipitation as hydroxides and sulfates. These processes may contribute to Co mobility in Faro waste-rock pile; however, the secondary mineralogical control on Co mobility is the subject of an ongoing assessment.…”
Section: Concentration-discharge Relationships In the Drainagementioning
confidence: 99%
“…The environmental pollution and risks of Mo area around mines have been heavily reported (Timofeev et al 2018;Song et al 2021). In non-mining areas, abnormally high Mo concentration in soils and aquatic system was found as a result of iron, alloys, ceramics, catalysts, lubricants and pigments production and agricultural fertilization (Smedley et al 2017;Ziwa et al 2020). The specific use of Mo in stainless steel is 1.1-2.9 kg/t worldwide (Outteridge et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(hydroxocobalamina) [54], la exposición excesiva al Co puede derivar en una amplia gama de afectaciones a la salud humana, tales como, el bocio y la reducción de la actividad tiroidea [55]. Este elemento se encuentra contenido en una gran variedad de residuos mineros procedentes de yacimientos de cobaltita (CoAsS), cattierita (CoS2), carrolita ((CuCo)2S4), sphaerocobaltita (CoCO3), cobaltpentlandita ((Co-Fe)9S8), siegenita ((Ni,Co)3S4), linnaeita (CoS4), esmaltita (CoAs2), safflorita ((Co,Fe)As2) y escuterudita ((Co,Fe,Ni)As2-3).…”
Section: Co (Cobalto)unclassified
“…Este elemento se encuentra contenido en una gran variedad de residuos mineros procedentes de yacimientos de cobaltita (CoAsS), cattierita (CoS2), carrolita ((CuCo)2S4), sphaerocobaltita (CoCO3), cobaltpentlandita ((Co-Fe)9S8), siegenita ((Ni,Co)3S4), linnaeita (CoS4), esmaltita (CoAs2), safflorita ((Co,Fe)As2) y escuterudita ((Co,Fe,Ni)As2-3). En condiciones bajas de pH estos minerales pueden disolverse y formar Co 2+ acuoso, mientras que, a un pH neutro, este Co acuoso puede inmovilizarse por precipitación y/o sorción en oxhidróxidos u óxidos de Fe y Mn [55].…”
Section: Co (Cobalto)unclassified